Soil Organic Matter as Catalyst of Crop Resource Capture - King, Alison E.; Ali, Genevieve A.; Gillespie, Adam W.; Wagner-Riddle, Claudia (Frontiers in Environmental Science, 2020)
The positive effect of soil organic matter (SOM) on crop yield has historically been attributed to the ability of SOM to supply crops with nitrogen and water. Whether management-induced increases in SOM meaningfully supplement water supply has received recent scrutiny, introducing uncertainty to the mechanisms by which SOM benefits crops. Here, we posit that to benefit crops SOM does not need to increase the supply of a growth-limiting resource; it only needs to facilitate root access to extant resource stocks. We highlight evidence for the ability of SOM to alleviate negative impacts of inadequate aeration (mainly waterlogging) and compaction on roots. Waterlogging, even if transient, can permanently downregulate root biosynthesis and call for expensive growth of new roots. Management practices that promote SOM reduce waterlogging by accelerating water infiltration and may promote aeration in non-saturated soils. Compaction as a restriction to root development manifests in drying soils, when mechanical impedance (MI) inflates photosynthate required to extend root tips, leading to short, thick, and shallow roots. SOM reduces MI in dry soils and is associated with root channels to subsoil, granting crops access to deep soil water. Both waterlogging and compaction necessitate additional belowground investment per unit resource uptake. In this framework, crop response to SOM depends on interactions of crop susceptibility to inadequate aeration or compaction, soil moisture, and “baseline” soil aeration and compaction status. By exploring the proposition that SOM catalyzes resource uptake by permitting root development, future research may constrain crop yield improvements expected from SOM management.